Compensatory justice to the victim of a crime and judicial practices in India: An empirical study - Sharma, Madhuker (International review of victimology, 2022)
The Constitution of India guarantees that justice shall be delivered to all. The duty to ensure that justice delivery is accessible to all is entrusted to state bodies. The legislature is expected to ensure that the legal framework is there, the executive is expected to ensure that all infrastructural needs of the justice delivery system are in place, and the judiciary is expected to ensure that justice is delivered in their area. This paper deals with the issue of delivery of victim justice, with a special focus on compensatory mechanisms laid down under the Code of Criminal Procedure 1973. The Code empowers the courts to award compensation to the victim of a crime to ensure his/her rehabilitation. In light of the observations made by the Supreme Court of India that the trial court judges do not exercise their discretionary power under the relevant statutory provisions to award compensation to the victims of a crime, this paper explores the extent of such failure and the reasons behind it.